Introduction of an antifungal stewardship programme targeting high-cost antifungals at a tertiary hospital in Cambridge, England. (25th February 2015) - Micallef, C.; Aliyu, S. H.; Santos, R.; Brown, N. M.; Rosembert, D.; Enoch, D. A.
Abstract: Background: Antifungal stewardship aims to promote the optimal use of antifungals through the careful selection of agents based on patient profile, target organism, toxicity, costs and the likelihood of emergence and spread of resistance. Methods: We report on an observational prospective 12 month study conducted by an antifungal stewardship team targeting the use of echinocandins (caspofungin and micafungin), voriconazole and liposomal amphotericin B in a tertiary referral hospital in the UK. Results: One-hundred-and-seventy-three patients were reviewed on 294 occasions. Clinical advice was given and implemented during review of 45 (88.2%) of micafungin prescriptions, 70 (78.7%) of those receiving voriconazole, 78 (62.4%) of those receiving liposomal amphotericin B and 3 (27.3%) of those receiving caspofungin. Except for voriconazole, nearly half of all treatments reviewed were stopped or changed. This study found that a crude cost saving of ∼£180 000 in antifungal drugs was generated compared with the previous year. Conclusions: Using a multidisciplinary team, antifungal stewardship can achieve significant improvements in patient management and it may reduce costs.